2014
DOI: 10.1371/journal.pone.0091183
|View full text |Cite
|
Sign up to set email alerts
|

Using Motor Imagery to Study the Neural Substrates of Dynamic Balance

Abstract: This study examines the cerebral structures involved in dynamic balance using a motor imagery (MI) protocol. We recorded cerebral activity with functional magnetic resonance imaging while subjects imagined swaying on a balance board along the sagittal plane to point a laser at target pairs of different sizes (small, large). We used a matched visual imagery (VI) control task and recorded imagery durations during scanning. MI and VI durations were differentially influenced by the sway accuracy requirement, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 68 publications
1
40
2
4
Order By: Relevance
“…In this line, the relatively long latency from the visual shift to the earliest changes in sway suggests the possibility that the process of visual integration for balance stabilization occurs at cortical level, since the cortex is certainly involved in controlling critical postures [7582]. …”
Section: Discussionmentioning
confidence: 99%
“…In this line, the relatively long latency from the visual shift to the earliest changes in sway suggests the possibility that the process of visual integration for balance stabilization occurs at cortical level, since the cortex is certainly involved in controlling critical postures [7582]. …”
Section: Discussionmentioning
confidence: 99%
“…The role of the midbrain in balance control is confirmed by studies using functional MRI and positron emission tomography, which have shown that the execution or motor imagery of postural tasks does not only activate cortical regions in the cerebellum and cerebrum, but also the midbrain [Ferraye et al, 2014;Ouchi et al, 1999]. It has been suggested that the midbrain is part of a network involving the cerebellum, frontal areas and thalamus working interactively to control dynamic balance [Ferraye et al, 2014].…”
Section: Associations Between Infratentorial Wm Volume and Postural Cmentioning
confidence: 92%
“…Control of balance and gait involves multiple supraspinal circuits that are partly distinct and partly overlapping . This presence of different underlying circuitries could explain why the effect of levodopa might differ for specific elements of balance and gait.…”
Section: Pseudoresistance To Dopaminergic Medicationmentioning
confidence: 99%